藉著晶圓接合從藍寶石基板上剝離氮化鎵發光二極體 - 吳耀銓; WU YEWCHUNG SERMON (My University, 2014)
本計畫是利用(1)在氮化鎵磊晶層與藍寶石基板間的產生凹凸狀的空隙結構。 加上 （2）晶圓接合後降溫時，造成在氮化鎵與藍寶石介面間的熱應力集中而剝離。主要有2 種方法:(1)濕式蝕刻藍寶石方式 (1)濕式蝕刻氮化鎵方式。磊晶後，再藉著晶圓接合從 藍寶石基板上剝離氮化鎵發光二極體。

This project is about lift-off GaN film using 2 steps: (1) reduced the interface between GaN and Sapphire substrate, and (2)separate them using wafer bonding processes. This is because the stress concentration on the interface. Two methods will be used (1) wet etched sapphire and (2) wet etched GaN.
Lift-off GaN LED Epitaxy Layer from Sapphire Substrate by Wafer Bonding Processes
Keywords: 剝離氮化鎵磊晶層; 晶圓接合; 濕式蝕刻藍寶石; 濕式蝕刻氮化鎵; lift-off GaN film; wafer bonding processes; wet etched sapphire; wet etched GaN